Research progress on the pathogenesis, clinical impact, and traditional Chinese medicine treatment of polycystic ovary syndrome complicated by insulin resistance - Sun, Zepu; Jin, Bao; Han, Han; Qin, Zhen; Shi, Yuqian; Zhang, Yuehui (Frontiers in Pharmacology, 2025)
BackgroundPolycystic ovary syndrome (PCOS) is one of the most common reproductive endocrine disorders affecting women of reproductive age. Insulin resistance (IR) is both a hallmark clinical feature and a key contributor to the pathophysiology of PCOS. Currently, metformin, along with other pharmaceuticals and lifestyle modifications, constitutes the primary approach to enhancing IR in PCOS. Despite demonstrating efficacy, some individuals exhibit suboptimal responses, and prolonged usage may lead to gastrointestinal side effects and other constraints. As an important complementary alternative medicine, recent research has highlighted traditional Chinese medicine (TCM) as a valuable adjunctive therapy for ameliorating IR in PCOS. The integration of TCM into the management of PCOS-related IR offers diverse therapeutic avenues, warranting comprehensive categorization and analysis.AimThis review systematically summarizes the pathogenesis and TCM interventions of IR in PCOS and its adverse clinical effects on patients at various stages. It primarily focuses on recent research findings, encompassing both animal studies and human studies, regarding the efficacy of TCM in ameliorating PCOS in conjunction with IR over the past 5 years.MethodsThis article collects relevant literature from databases such as PubMed, Web of Science, Embase, and Cochrane Library from the establishment to 2025. The search utilized the following keywords: Polycystic ovary syndrome, Insulin resistance, Polymorphism, Genetic, Epigenomics, Hyperandrogenism, Inflammation, Microbiota, Mitochondria. This review focuses on recent literature published within the last 5 years to maintain the research’s contemporary relevance. Additionally, classical studies are incorporated to uphold the theoretical framework’s integrity.ResultsThe current evidence indicates that TCM contributes to the management of PCOS with IR primarily through modulation of gut microbiota equilibrium, suppression of inflammatory reactions (including reduction of inflammatory cytokines), amelioration of hyperandrogenism, and modulation of insulin signaling pathways.ConclusionThis review examines current research on the treatment of PCOS complicated by IR using TCM. The findings confirm the efficacy of TCM in ameliorating IR. Discrepancies in dosages and treatment durations of TCM compounds and monomers, as well as batch-to-batch variability in TCM quality, may impact treatment efficacy. Additionally, the translation of animal study outcomes to clinical settings remains unvalidated, necessitating further investigation into the synergistic effects of combined TCM and modern medicine approaches. Future efforts should focus on establishing standardized research protocols and quality control measures, enhancing the evidence base for integrated TCM and Western medicine treatments, and facilitating the translation of basic research findings into clinical practice. These steps are crucial for optimizing the role of TCM in managing PCOS-IR.